Prevention of social stress-escalated cocaine self-administration by CRF-R1 antagonist in the rat VTA - Boyson, Christopher O.; Miguel, Tarciso T. [UNESP]; Quadros, Isabel M.; DeBold, Joseph F.; Miczek, Klaus A. (Springer, 2011)
Intermittent exposure to social defeat stress can induce long-term neural plasticity that may influence escalated cocaine-taking behavior. Stressful encounters can lead to activation of dopamine neurons in the ventral tegmental area (VTA), which are modulated by corticotropin releasing factor (CRF) neurons.The study aims to prevent the effects of intermittently scheduled, brief social defeat stress on subsequent intravenous (IV) cocaine self-administration by pretreatment with a CRF receptor subtype 1 (CRF-R1) antagonist.Long-Evans rats were submitted to four intermittent social defeat experiences separated by 72 h over 10 days. Two experiments examined systemic or intra-VTA antagonism of CRF-R1 subtype during stress on the later expression of locomotor sensitization and cocaine self-administration during fixed (0.75 mg/kg/infusion) and progressive ratio schedules of reinforcement (0.3 mg/kg/infusion), including a continuous 24-h "binge" (0.3 mg/kg/infusion).Pretreatment with a CRF-R1 antagonist, CP 154,526, (20 mg/kg i.p.) prior to each social defeat episode prevented the development of stress-induced locomotor sensitization to a cocaine challenge and prevented escalated cocaine self-administration during a 24-h "binge". In addition, pretreatment with a CRF-R1 antagonist (0.3 mu g/0.5 mu l/side) into the VTA prior to each social defeat episode prevented stress-induced locomotor sensitization to a cocaine challenge and prevented escalated cocaine self-administration during a 24-h "binge".The current results suggest that CRF-R1 subtype in the VTA is critically involved in the development of stress-induced locomotor sensitization which may contribute to escalated cocaine self-administration during continuous access in a 24-h "binge".
Keywords: Stress; Locomotor sensitization; Escalated cocaine self-administration; CRF-R1; CP 154,526; VTA